Pragmatic Approach to Use of Mastery Learning Model in Implementation of Social Studies Curriculum for Achievement of Sustainable Development Goal-4 in Nomadic Schools in Maiadua, Katsina State, Nigeria - Francis, Torpev Terver (NIU Journal of Humanities, 2023)
Acquisition of quality education for all is one of the basic concerns of societies in the world.  This desire is anchored on universal protocol agreement contained in sustainable development goal four (quality education for all). The paper is therefore an attempt to investigate pragmatic approach to use of mastery learning model in implementation of social studies curriculum for achievement of sustainable development goal-4 in nomadic schools in maiadua, katsina state, Nigeria. A descriptive research design involving pre-test and post-test was used for the study. The population of the study was 78 headmasters in the 78 primary schools in the Local government area. Sample for the study was all the 78 headmasters who were purposively selected by virtue of their leadership positions in the schools. A Researcher designed questionnaire was used in data collection. The instrument was validated by two experts in test and measurement and one curriculum expert who were of the rank of senior lecturer and above. Reliability of the instrument was ensured by administering the instrument twice to 30 headmasters in Kurfi local government at interval of two weeks. The data collected was analysed using Pearson moment correlation coefficient. The coefficient of 0.67 was obtained which show that the instrument was reliable. Two objectives with corresponding research questions and hypotheses were raised and formulated respectively to guide the study. The research questions were answered using descriptive statistics: frequency count and percentage, while the hypotheses were tested using chi-square statistic at 0.05 level of significance. The findings of the study revealed that: headmasters’ perception of mastery learning was positive as most of them responded positive to the items on the instrument, they had knowledge of mastery learning instructional model in implementation of Social studies curriculum in Nomadic schools in maiadua, Katsina State, Nigeria, they attempted to put to use knowledge of mastery learning in implementation of Social Studies curriculum in Nomadic schools Katsina State, Nigeria, however they lacked the modern technique used in achievement of the instructional model. Based on the findings the following recommendations were made: deliberate effort should be made to improve the skills of teachers on the acquisition and use of mastery learning instructional strategy by ministry of education through organization of workshops and conferences for the teachers in basic schools. Mastery learning instructional strategy should be given prominence in teacher education programmes in higher tertiary institutions to enable the pre-service teachers acquire necessary knowledge and skill on the strategy and fresh graduates from Colleges of Education employed in nomadic schools should be sensitized on the benefits of mastery learning instructional strategy by school administrators using symposium and other available means to avoid attrition.